Sejarah Dan Perkembangan Industri Media Islam Di Indonesia - Mirza Azkia Muhammad Adiba (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah IAI Uluwiyah Mojokerto, 2020)
The mass media in its history has always played an important role for a nation, group, group, and even religion. Indonesia has an Islamic mass media, the value of its heritage is valuable, especially those with Islamic ideology that have provided an important civilization legacy. This article examines the history of Islamic media in Indonesia from the colonial era to the present. Then it examines the industry and its challenges. These two aspects will be discussed in in-depth writing, examples of media names and their contents will be discussed. To review this discussion, the authors used literature studies obtained from various sources. In this study it can be concluded that the presence of Islamic media is exposed by readers and the attractiveness of rubrics or content presented by the editors of Islamic media.